Energy Saving Strategy for Video-based Wireless Sensor Networks Under Field Coverage Preservation - Pescaru, D.; Istin, C.; Curiac, D.; Doboli, A. (2008 IEEE International Conference on Automation, Quality and Testing, Robotics, 2008)
The demand for video-based wireless sensor networks (WSN) applications has significantly increased. Different from conventional sensor networks, video WSN imply a directional sensing model, complex in-node processing, and large data transfer, thus high clock frequencies and significant radio transmission time. Reducing energy consumption is a key requirement for reliable applications. We propose in this paper a novel energy saving method based on redundant node deactivation while preserving field coverage.